2020
DOI: 10.3390/brainsci10070414
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Based Cognitive Rehabilitation in Minimally Conscious State: A Case Report with EEG Findings and Systematic Literature Review

Abstract: Chronic disorders of consciousness cause a total or partial and fluctuating unawareness of the surrounding environment. Virtual reality (VR) can be useful as a diagnostic and/or a neurorehabilitation tool, and its effects can be monitored by means of both clinical and electroencephalography (EEG) data recording of brain activity. We reported on the case of a 17-year-old patient with a disorder of consciousness (DoC) who was provided with VR training to improve her cognitive-behavioral outcomes, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…aEEG is the average value of the upper and lower boundaries of EEG amplitude, which directly reflects the severity of brain injury. A previous study has shown that VR training significantly improved both clinical and neurophysiological outcomes in patients with DOC, and the EEG plus VR approach used for patients with DOC could be promising to define the most appropriate stimulation protocol ( 29 ). Our results also suggest that VR training may improve aEEG in patients with DOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aEEG is the average value of the upper and lower boundaries of EEG amplitude, which directly reflects the severity of brain injury. A previous study has shown that VR training significantly improved both clinical and neurophysiological outcomes in patients with DOC, and the EEG plus VR approach used for patients with DOC could be promising to define the most appropriate stimulation protocol ( 29 ). Our results also suggest that VR training may improve aEEG in patients with DOC.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that visual and auditory stimulation based on VR is safe and has great potential in reducing psychological burden and restoring cognition and attention of critically ill patients ( 33 ). A recent case study reported a 17-year-old patient with DOC who received cognitive rehabilitation training with semi-immersive VR, and the results showed that both clinical and neurophysiological parameters were significantly improved ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strategies of telerehabilitation (Zucchella et al, 2018 ; Raso et al, 2021 ) might be implemented. Moreover, cognitive and motor rehabilitation solutions may be embedded (Maggio et al, 2020 ; Daibert-Nido et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, AR may be viewed as easier to use because it refers to I-PAD, tablets, and smartphones, which are more suitable to the real world (Bekkers et al, 2020 ; Held et al, 2020 ; Levin and Demers, 2021 ). Although widely used in patients with disorders of consciousness (Hinze et al, 2021 ; Kwok et al, 2021 ), to the best of our knowledge it has never been used in patients with acquired brain injuries, history of coma and post-coma outcomes, except for the contribution of Maggio et al ( 2020 ). Although it may be considered as ethically controversial and questionable, such hypothesis undoubtedly merits to be empirically tested, eventually integrated with an assistive technology device, for both assessment and recovery goals.…”
Section: Virtual Realitymentioning
confidence: 99%
“…This is because they are useful as a diagnostic and/or rehabilitation tool, and their effects can be monitored by recording both clinical and electroencephalographic data. For example, in [ 87 ] the case of a 17-year-old patient is presented. She had a disorder of consciousness (DoC), and a VR training to improve her cognitive-behavioral outcomes which were assessed using clinical scales was presented.…”
Section: Discussionmentioning
confidence: 99%